2011
DOI: 10.1093/nar/gkr680
|View full text |Cite
|
Sign up to set email alerts
|

Guiding strand passage: DNA-induced movement of the gyrase C-terminal domains defines an early step in the supercoiling cycle

Abstract: DNA gyrase catalyzes ATP-dependent negative supercoiling of DNA in a strand passage mechanism. A double-stranded segment of DNA, the T-segment, is passed through the gap in a transiently cleaved G-segment by coordinated closing and opening of three protein interfaces in gyrase. T-segment capture is thought to be guided by the C-terminal domains of the GyrA subunit of gyrase that wrap DNA around their perimeter and cause a DNA-crossing with a positive handedness. We show here that the C-terminal domains are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 32 publications
4
68
0
Order By: Relevance
“…6A,B; Kirchhausen et al 1985;Costenaro et al 2005;Lanz and Klostermeier 2011). Scattering data obtained for gyrase DCTD in the absence of YacG showed that the protein adopted an extended conformation with a significantly greater radius of gyration (R g ) than that seen for samples prepared with YacG (R g, gyrase = 90.3 Å 6 1.7 Å vs. R g, gyrase•YacG = 62.8 Å 6 2.7 Å ) (Fig.…”
Section: Yacg Induces Atpase Domain and Dna Gate Closure In The Gyrasmentioning
confidence: 93%
“…6A,B; Kirchhausen et al 1985;Costenaro et al 2005;Lanz and Klostermeier 2011). Scattering data obtained for gyrase DCTD in the absence of YacG showed that the protein adopted an extended conformation with a significantly greater radius of gyration (R g ) than that seen for samples prepared with YacG (R g, gyrase = 90.3 Å 6 1.7 Å vs. R g, gyrase•YacG = 62.8 Å 6 2.7 Å ) (Fig.…”
Section: Yacg Induces Atpase Domain and Dna Gate Closure In The Gyrasmentioning
confidence: 93%
“…The isolated CTD binds DNA via an elongated patch of positively charged amino acids around its perimeter, resulting in DNA bending and introduction of positive writhe (22,24). In gyrase, the CTDs associate with DNA adjacent to the G-segment that extends from the DNA-gate on the enzymatic core (26,27). Contact formation between these DNA regions and the CTDs is accompanied by a repositioning of the CTDs, aligning them with the DNA-gate (26).…”
mentioning
confidence: 99%
“…In gyrase, the CTDs associate with DNA adjacent to the G-segment that extends from the DNA-gate on the enzymatic core (26,27). Contact formation between these DNA regions and the CTDs is accompanied by a repositioning of the CTDs, aligning them with the DNA-gate (26). The geometry imposed on the DNA by the CTDs directs the DNA exiting from the CTDs toward the N-gate in an orientation that allows the flanking region to serve as a T-segment for strand passage (15,26,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…causes the CTDs to move upward and sideways (9), and complete wrapping of DNA leads to narrowing of the N-gate formed by the GyrB subunits (8). The N-gate acts as an ATPdependent clamp (10): ATP binding to the ATPase domains of the GyrB subunits induces GyrB dimerization and N-gate closure (8,(11)(12)(13), leading to the trapping of the transport DNA (T-segment).…”
mentioning
confidence: 99%